The Relationship of Self-Control with Academic Procrastination of State High School Students 3 Polewali - Putriani, Salsabila Eka; Razak, Ahmad (Polteknik Ilmu Pemasyarakatan, 2025)
Each student is expected to be able to manage their time well to complete their tasks. However, there are still many students who tend to procrastinate and spend time when given schoolwork. This study aims to see the relationship between self-control and academic procrastination in high school 3 polewali students. The sampling technique uses the accidental sampling technique and uses a quantitative research method with a total of 300 respondents. The results showed that there was a negative relationship between self-control and academic procrastination with a correlation of r = -217 and a significant value of 0.000 (p < 0.05). This means that the higher the self-control possessed by students, the lower the academic procrastination behavior carried out by students. The implication of this study is that it can contribute to the development of science related to academic procrastination and self-control and can be a guideline for students and teaching staff to improve self-control and avoid academic procrastination behavior.